Chasing embers - Beck, Glenn; Hedrick, Mikayla G. (Beck, Glenn. Oarsmen, 2024)
"In a new world run by Topos, Inc., the United States of America only exists as a fading memory. On the path to utopia, the pillars of culture--religion, art, history, and science--have been decimated. The past is dead, and Topos killed it. Sixteen-year-old Ember remembers the day her parents were taken by Topos seven years ago. The only possession she has from them is a leather notebook containing the history of the world--contraband that could send her straight to Sleep Camp. When Ember is selected to serve on Topos's task force to reduce underage extremism, she has one chance to start a new life, but it may cost her everything. Seventeen-year-old Sky has run away to a town of savage Holdouts who refuse to live under the rule of Topos--and who might be able to tell him if his whole life has been a lie. As the Holdouts slowly but surely win Sky over, he must decide what 'true' really means, and if the truth even matters in a world ruled by an absolute power. As they carry their secrets, Ember and Sky become unintended accomplices to a secret society plotting to overthrow Topos. And when they find themselves on the wrong side of the most powerful corporation on earth, they have two options: beat them or join them."--